(untitled) (Международный научный журнал «Инженер», 2026)
The article analyzes the role of composite binders in improving the operational characteristics of high-quality concrete. It highlights the impact of materials such as fly ash, slags, and polymers on the quality, strength, and durability of concrete. The potential for improving concrete quality through the application of these technologies in Uzbekistan’s construction industry is also discussed.